Perubahan Perilaku Konsumsi Masyarakat Kota Gresik dari Pasar Modern ke Online Shop dimasa Pandemi Covid-19 - Falahiyah, Khilda; Hariyanto, Sugeng (Prodi Manajemen Fakultas Ekonomi dan Bisnis Universitas Islam Raden Rahmat Malang, 2022)
This study aims to analyze changes in the consumption behavior of the people of Gresik city from the modern market to the online shop. In this study using a descriptive qualitative approach. The nature of the writing is descriptive, the research subject is the people who live in Gresik Regency GKB Housing located in Gresik Regency. Data collection techniques use primary and secondary data, primary data in the form of observations and interviews, while secondary data comes from journals, articles, books and others. Data analysis uses descriptive analysis with data reduction, data presentation, and data verification methods. The results of the study show that the change in the consumption pattern of the people of Gresik city from a modern market to an online shop was triggered by covid-19, where the pandemic period required the public to comply with health protocols and PPKM policies which made people locked out of their homes and interacted in order to break the spread. covid-19. With the COVID-19 pandemic and the support of the increasingly rapid development of information technology, people are more likely to consume or shop online rather than buying goods at the right place, such as shops, malls, supermarkets, and minimarkets. This has created a change in the consumption pattern of the people of the city of Gresik.